1991
DOI: 10.1159/000099553
|View full text |Cite
|
Sign up to set email alerts
|

Heavy-Charged-Particle Radiosurgery of the Pituitary Gland: Clinical Results of 840 Patients

Abstract: Since 1954, 840 patients have been treated at Lawrence Berkeley Laboratory with stereotactic charged-particle radiosurgery of the pituitary gland. The initial 30 patients were treated with proton beams; the subsequent 810 patients were treated with helium ion beams. In the great majority of the 475 patients treated for pituitary tumors, marked and sustained biochemical and clinical improvement was observed. Variable degrees of hypopituitarism developed in about one-third of patients treated solely with radiosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(46 citation statements)
references
References 11 publications
(30 reference statements)
1
42
0
3
Order By: Relevance
“…The limited data on the use of gamma knife surgery (GKS) in Nelson's syndrome are conflicting (78)(79)(80)(81). Although one study of Nelson's syndrome patients showed no tumour re-growth at 7 years post GKS therapy (82), a further study showed remission rates post GKS to be only 14% (83).…”
Section: Stereotactic Radiosurgerymentioning
confidence: 99%
“…The limited data on the use of gamma knife surgery (GKS) in Nelson's syndrome are conflicting (78)(79)(80)(81). Although one study of Nelson's syndrome patients showed no tumour re-growth at 7 years post GKS therapy (82), a further study showed remission rates post GKS to be only 14% (83).…”
Section: Stereotactic Radiosurgerymentioning
confidence: 99%
“…There are relatively few studies detailing the results of radiosurgery for Nelson's syndrome (Table 6) ( Ganz, 2000;Ganz et al, 1993;Kobayashi et al, 2002;Laws & Vance, 1999;Levy et al, 1991;Mauermann et al, 2007;Pollock & Wolffenbuttel et al, 1998;Young, 2002). These studies report a mean tumor dose from between 12 Gy to 28.7 Gy, and an endocrine remission rate ranging from 0% to 36%, although only a minority of these studies defined what was meant by endocrine remission.…”
Section: Rsxmentioning
confidence: 99%
“…This method of irradiation was widely used for treatment of acromegaly in the 1960s and 1970s. 33,45,56 Its popularity, however, waned as more advanced technologies, such as GKS, were optimized for less frequent side effects. 6,59,83 Still, interest in this modality remains, and the treatment continues to be studied at the 7 proton beam centers in the US.…”
Section: Proton-beam Radiosurgerymentioning
confidence: 99%
“…2,56,97 Since that time, substantial advances in radiation technology have yielded increasingly precise pituitary adenoma-targeting capability and consequently an expanded set of treatment options for acromegaly to supplement resection and hormonal suppression with medical management. A complex array of factors dictate treatment decisions for acromegaly in the modern era, including adenoma size, degree of secretory hyperactivity, invasion of surrounding structures, and therapeutic side effects and their particular impact in the patient in question.…”
mentioning
confidence: 99%